Collaboration/participation/friendship in research: formative evaluation in practice - Stehlik, Daniela; Chenoweth, L. (Association of Qualitative Research (RMIT Publishing ), 2005)
A participatory research project undertaken in Queensland offered a unique opportunity to reflect on research as 'praxis' - that is, as an integration of collaboration/participation/friendship within the methodology itself. The place of friendship is largely overlooked in any analysis of research collaboration. Drawing on their decade-long partnership, the authors restate the importance of not only participation and reflexivity, but also the strengths that a research friendship can bring to the broader project. Building on literature which contextualises the findings of their research, the paper outlines the broader research methodology and the process by which the concept of 'praxis' has been clarified through the description of a case study. It touches on the strengths, limitations and joys of such a process, and reflects on its capacities in the broader qualitative research field.